Early Response after Catheter Ablation of the Epicardial Substrate in a Patient with Brugada Syndrome Can Be Predicted by High Precordial Leads - Yae Min Park; Mi Sook Cha; Hanul Choi; Woong Chol Kang; Seung Hwan Han; In Suck Choi; Eak Kyun Shin; Young-Hoon Kim (Case Reports in Cardiology)
A 52-year-old male with Brugada syndrome presented with repeated and appropriate shock from an implantable cardioverter defibrillator (ICD). Catheter ablation for substrate elimination targeting low-voltage, complex, and fractionated electrocardiograms and late potentials in the epicardial right ventricular outflow tract was successfully performed. Brugada phenotype in the right precordial leads from the third intercostal space disappeared in the early stage after catheter ablation and that from the standard fourth intercostal space disappeared later. He remained free from ventricular fibrillation over the next fourteen months. We suggest that this novel ablation strategy is effective in Brugada syndrome patients with ICD, and early response after catheter ablation can be predicted by high precordial leads.